(untitled) - Burleigh, Robert (New York, 2002)
Traces the history of chocolate from a drink of the Olmec and Maya and later in Europe to its popularity around the world today.
Keywords: Chocolate; Juvenile literature; Cookery (Chocolate); Juvenile literature; Chocolate